2020
DOI: 10.18632/oncotarget.27461
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind trial of F14512, a polyamine-vectorized anticancer drug, compared with etoposide phosphate, in dogs with naturally occurring lymphoma

Abstract: Copyright: Boyé et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACTPurpose: F14512 is an epipodophyllotoxin derivative from etoposide, combined with a spermine moiety introduced as a cell delivery vector. The objective of this study was to compare the safety and antitumor activity of F14512 and eto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This study was part of a comparative oncology project assessing a new polyamine‐vectorized anticancer drug (F14512) compared with the parent drug etoposide, in dogs with naturally occurring NHL 47 . The study design was prospective, randomized and double‐blinded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was part of a comparative oncology project assessing a new polyamine‐vectorized anticancer drug (F14512) compared with the parent drug etoposide, in dogs with naturally occurring NHL 47 . The study design was prospective, randomized and double‐blinded.…”
Section: Methodsmentioning
confidence: 99%
“…All dogs were staged based on the modified WHO five‐stage criteria for canine lymphoma as previously described 47 . Initial staging tests included a complete blood count, blood smear evaluation, biochemistry panel, ionized calcemia, whole‐body computed tomography, fine‐needle aspirates (FNA) and biopsies of peripheral lymph nodes, ultrasound‐guided liver and spleen FNA, urine analysis and bone marrow aspirates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is to be mentioned that spermine has also been utilized as a vector molecule for increasing the cellular uptake of the anticancer agent with clinical success. 32 Moreover, spermine, being a nonamino acid entity, could contribute to the proteolytic stability of the peptidomimetics. Previously, we also reported spermineconjugated novel antimicrobial peptidomimetics having tryptophan and phenylalanine residues in their templates for targeting the cell membrane of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…Research in comparative oncology has demonstrated that naturally occurring canine cancers are of valuable and translatable interest for the understanding of human cancer biology and characterization of new therapies [1][2][3][4]. Osteosarcoma is the most common primary bone tumor reported in both human and companion dog populations [5,6].…”
Section: Introductionmentioning
confidence: 99%